α-SMA Expression Increased Over Cell Passages and Decreased by Exogenous TGF-β1, In Vitro Studies on Myofibroblast Derived from Orbital Socket Contracture - Debby Shintiya Dewi; Elsa Safira Chairinnisa; Hidayat Sujuti; Diana Lirawati; Tinny Endang Hernowati (Journal of Tropical Life Science, 2018)
α-smooth muscle actin (α-SMA), a marker of myofibroblast, induces cytoskeleton reorganization, increases contractility and stimulates cell migration in TGF-β1 induced stress fibers. The aims of the present study were to determine the level of α-SMA expression and morphological cell changes in different passages of myofi-broblasts with varied TGF-β1 concentrations. Myofibroblast cell cultures were derived from fibrotic tissues of fourth degree socket contracture. The α-SMA expression level was measured in myofibroblast cultures pas-sage I, II, and III with and without 10 ng/mL TGF-β1, and in passage III with 2.5; 5; 10; and 20 ng/mL TGF-β1. Results: The levels of α-SMA expression level in passage I to III were I 31.42 ± 3.4; 40.34 ± 8.14 and 56.37 ± 7.57, respectively. Addition of 10 ng/mL TGF-β1 into passage I-III myofibroblast cultures resulted in α-SMA expression level of 31.24 ± 2.93; 36.81 ± 6.09; and 14.29 ± 2.72, respectively. Myoblasts passage III showed the lowest α-SMA expression level following exposure to TGF-β1 10 ng/mL (22.37 ± 12.86) and highest without TGF-β1 (48.34 ± 13.36), however no morphological changes detected. α-SMA expression level increased with cell passages, decreases with addition of TGF-β1 while not affecting morphology of myofibroblast derived from the orbital socket contracture.